2021
DOI: 10.3390/land10101034
|View full text |Cite
|
Sign up to set email alerts
|

Shoreline Evolution and Environmental Changes at the NW Area of the Gulf of Gela (Sicily, Italy)

Abstract: Coastal areas are among the most biologically productive, dynamic and valued ecosystems on Earth. They are subject to changes that greatly vary in scale, time and duration and to additional pressures resulting from anthropogenic activities. The aim of this work was to investigate the shoreline evolution and the main environmental changes of the coastal stretch between the towns of Licata and Gela (in the Gulf of Gela, Sicily, Italy). The methodology used in this work included the analysis of: (i) shoreline cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The coastal lacustrine-palustrine system (called "Pantani di Vendicari") consists of three flooded coastal lakes and is flanked on land by widespread karst forms [18]. The evolution of the In agreement with the analytical approach of numerous studies in the Mediterranean area [47][48][49][50] and from other different parts of the world [10,[51][52][53][54][55], our geomorphological study took into consideration the evaluation of three main factors: (i) the lithology of the substratum; (ii) the rate of sea level rise; and (iii) the rate of sediment supply.…”
Section: Northern Sector: Barrier-lagoon Systemsmentioning
confidence: 82%
“…The coastal lacustrine-palustrine system (called "Pantani di Vendicari") consists of three flooded coastal lakes and is flanked on land by widespread karst forms [18]. The evolution of the In agreement with the analytical approach of numerous studies in the Mediterranean area [47][48][49][50] and from other different parts of the world [10,[51][52][53][54][55], our geomorphological study took into consideration the evaluation of three main factors: (i) the lithology of the substratum; (ii) the rate of sea level rise; and (iii) the rate of sediment supply.…”
Section: Northern Sector: Barrier-lagoon Systemsmentioning
confidence: 82%
“…Molina et al [86] attribute the results of coastal erosion to local conditions and state that the erosion rate classifications should not be the same for each place. Borzi et al [87] present three factors as the main modulators of coastal erosion and clustered under specific characteristics: deltas (rivers), the dune-beach relationship, and protection infrastructure. The results of Molina et al [88] showed clustering in deltas, pocket beaches, and infrastructure zones.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent times, the extensive man‐made modifications of coasts and lands, that is, ports, coastal defence structures and human settlements, become key factors in triggering coastal dynamic changes (Chu et al, 2020; Di Stefano et al, 2013; Fletcher et al, 2012). As such, many studies on shoreline changes throughout the world have been carried out over the last few years (Aladwani, 2022; Bacino et al, 2020; Borzì et al, 2021; Quang, Linh et al, 2021). Shoreline change analysis methods that have been applied worldwide comprise the use of video images introduced by Holman et al (1993), Plant and Holman (1997) and Lippmann and Holman (1989), numerical modelling by applying continuity equation in LITPACK software (Rezaee et al, 2019), and computation of End Point Rate (EPR), Linear Regression Rate (LRR) and Weighted Linear Regression Rate (WLR) statistical parameters from image analysis utilizing Digital Shoreline Analysis System (DSAS) software (Johnston et al, 2023; Laksono, Borzì et al, 2022; Santos et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean area, the long‐ and medium‐term coastal retreat emerged to be the result of persistent sediment budget alterations, as response mainly to riverine sediment discharge decrease and longshore transport changes due to the harbours or coastal defence structures emplacement (Borzì et al, 2021). The Augusta Bay is one of the primary harbour and oil refinery areas in Italy and significantly contributes to the Italian economy (Margheriti, 2021; Selvaggi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%